Clinico-Pathological Co-relation in Diagnosis and Management of Abnormal Uterine Bleeding - BC, Durga; Sharma, Nirmala (Journal of Nepalgunj Medical College, 2019)
Abnormal uterine bleeding is the third most common clinical presentation in gynecology OPD. Histopathological evaluation of the endometrial tissue plays a significant role in diagnosis and management of Abnormal Uterine Bleeding. Aim: To find out cause of abnormal uterine bleeding with the help of histopathological report of endometrial biopsy. Methodology: This is retrospective observational study done at NGMC from ( 1st June 2018 to -30th June 2019) of 100 patients endometrial biopsy sent for histopathological evaluation and diagnosis reports were correlated with age and bleeding pattern and patients were managed accordingly. Result: A total of 100 endometrial specimens submitted with clinical diagnosis of Abnormal Uterine Bleeding were studied. Patients age group ranged from 18 – 65 yrs and most of them were seen in the age group of 41–50 yrs (43%).The commonest complaint was menorrhagia i.e. 48% .The commonest endometrial pattern observed in the study was, proliferative phase endometrium (38%). Conclusion: Endometrial biopsy is one of the most useful diagnostic tools to find out cause of uterine bleeding in AUB cases and also helps in management of AUB patient.